If it's not what You are looking for type in the equation solver your own equation and let us solve it.
5(x-2)=(2x-2)
We move all terms to the left:
5(x-2)-((2x-2))=0
We multiply parentheses
5x-((2x-2))-10=0
We calculate terms in parentheses: -((2x-2)), so:We get rid of parentheses
(2x-2)
We get rid of parentheses
2x-2
Back to the equation:
-(2x-2)
5x-2x+2-10=0
We add all the numbers together, and all the variables
3x-8=0
We move all terms containing x to the left, all other terms to the right
3x=8
x=8/3
x=2+2/3
| 9y+5+2y+3=16y-12+4y | | a/5+3=1 | | 63=28-5(x-4) | | 9y+5+2y+3=16y-12 | | -p/5=14 | | 23h−13h+11=8h | | F(×)=×^2-5x-8 | | -2(-5+6x)=-2 | | F(×)=×^2-5x+8 | | 2-3x/4=12 | | 3y+15=32 | | 3x+800=7x | | 25=y-11* | | -2(2f+8)=-4(-f+2 | | 8x+11=2(4×-7)+25 | | 2x+(x+1)^(1/2)=8 | | 5z–13=7 | | 4x-36=x=24 | | 2x-4x-14=2x+5-14 | | −(1−3x)+2(2x−1)=−17= | | 2+.25x=9.75 | | 5x-1=x+63 | | t/÷0.3=1.4 | | (2x=3x)+(x-6)=180 | | 28=5a-2a+3 | | −(1−3x)+2(2x−1)=−17 | | 4/5(1/3n+2/3)=-3 | | 32=15+3y | | (2x=3x)=180 | | 2-(x-7)=33 | | 12x-6x-30=2x+3x-20 | | 5x(3x+5)=690 |